2012
DOI: 10.1186/1475-2840-11-105
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin attenuates cardiac dysfunction by increasing myocardial angiogenesis and inhibiting interstitial fibrosis in diabetic rats

Abstract: BackgroundRecent studies revealed that erythropoietin (EPO) has tissue-protective effects in the heart by increasing vascular endothelial growth factor (VEGF) expression and attenuating myocardial fibrosis in ischemia models. In this study, we investigated the effect of EPO on ventricular remodeling and blood vessel growth in diabetic rats.MethodsMale SD rats were randomly divided into 3 groups: control rats, streptozotocin (STZ)-induced diabetic rats, and diabetic rats treated with 1000 U/kg EPO by subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…Lu et al [24] reported that epoetin beta inhibits cardiac fibrosis in the experimental diabetes model. Recently, Geng et al [25] reported that epoetin ameliorates renal interstitial fibrosis in the experimental unilateral ureteral obstruction model.…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al [24] reported that epoetin beta inhibits cardiac fibrosis in the experimental diabetes model. Recently, Geng et al [25] reported that epoetin ameliorates renal interstitial fibrosis in the experimental unilateral ureteral obstruction model.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of TT-1 on the Bax, Bcl-2, caspase-3 and caspase-9 RNA expression in TT cells were examined by RT-qPCR as previously described (25,26). Total RNA was extracted from TT cells with or without TT-1 treatment (0-8 µg/ml for 48 h) by using Trizol reagent and then purified with an RNeasy Mini kit (Qiagen GmbH, Hilden, Germany).…”
Section: Quantitative Reverse Transcription Polymerase Chain Reactionmentioning
confidence: 99%
“…For capillary density measurement, endothelial cells were stained with CD31, which is often used as a biological marker to represent capillary vessels in the myocardium [17]. Immunohistochemistry was performed using rabbit anti-rat CD31 antibody (Santa Cruz Biotechnology, USA, 1:100), and the staining was visualized by reaction with DAB (Sigma Chemical Co., USA, 1:20).…”
Section: Measurement Of Capillary Densitymentioning
confidence: 99%
“…Immunohistochemistry was performed using rabbit anti-rat CD31 antibody (Santa Cruz Biotechnology, USA, 1:100), and the staining was visualized by reaction with DAB (Sigma Chemical Co., USA, 1:20). Capillaries were identified by a brown round structure with a central lumen and a diameter <20μm and a layer of endothelial cells without smooth muscle cells in the myocardium under a light microscope (magnification, 400X) (17) . Five fields on the slide were randomly chosen for counting the stained capillaries.…”
Section: Measurement Of Capillary Densitymentioning
confidence: 99%